2016
DOI: 10.1017/s1431927615015585
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aortic Collagen Fiber Angle Distribution in Mouse Models of Atherosclerosis Using Second-Harmonic Generation (SHG) Microscopy

Abstract: Characterization of collagen fiber angle distribution throughout the blood vessel wall provides insight into the mechanical behavior of healthy and diseased arteries and their capacity to remodel. Atherosclerotic plaque contributes to the overall mechanical behavior, yet little is known experimentally about how collagen fiber orientation is influenced by atherogenesis. We hypothesized that atherosclerotic lesion development, and the factors contributing to lesion development, leads to a shift in collagen fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The skeletonization of the vessel likely results in the activation of adventitial fibroblasts, leading to a change in ECM production and organization, especially medial elastin, which have profound effects on vessel function . Interestingly, alterations in collagen play a significant role in vessel stiffening associated with the development of aneurysms, atherosclerosis, and hypertension . The changes in both elastin and collagen organization noted in our study suggest that the decrease in cyclic strain in skeletonized vessels is due to either a reduction in elastic recoil during diastole associated with elastin disruption, reduced distension during systole associated with alterations in collagen, or both.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The skeletonization of the vessel likely results in the activation of adventitial fibroblasts, leading to a change in ECM production and organization, especially medial elastin, which have profound effects on vessel function . Interestingly, alterations in collagen play a significant role in vessel stiffening associated with the development of aneurysms, atherosclerosis, and hypertension . The changes in both elastin and collagen organization noted in our study suggest that the decrease in cyclic strain in skeletonized vessels is due to either a reduction in elastic recoil during diastole associated with elastin disruption, reduced distension during systole associated with alterations in collagen, or both.…”
Section: Discussionmentioning
confidence: 68%
“…Due to collagen's intrinsic properties such as optical anisotropy, fibril structure, and multifibril organization, collagen fibers and bundles were visualized in this study without labeling agents under SHG with femtosecond pulsed infrared excitation . The SHG technique offers many advantages for biomedical assessment of tissue structure, including visualization of collagen fibers without staining and deeper penetration within a sample when compared with conventional single‐photon excitation microscopy . SHG emission directionality is sensitive to the diameter of the fibrils that are bundled into collagen fibers, as well as their spacing within the fiber, and the disorder in their packing .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike confocal microscopy, multiphoton microscopy 3 with second harmonic generation (SHG) imaging requires no special preparation or staining of vessels. SHG imaging has previously been used to interrogate fibre orientation through a vessel thickness (Keyes et al, 2011;Watson et al, 2016) and in response to physiological and biaxial loading (Keyes et al, 2011) of mouse aortic tissue without the separation of layers. However, given the limited depth of penetration of such imaging techniques, they cannot be used for imaging the full intact wall, or even intact layers, of thicker vessel walls such as porcine carotid arteries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, collagen content and orientation measurement successfully differentiated two histologic types of fibroadenoma tissue and normal breast tissue in one study (Nie et al ., ), and in other study quantification of collagen structure in breast biopsies showed promising results for distinguishing malignant from nonmalignant breast tissue conditions (Ambekar et al ., ). Recent studies have also measured the orientation of collagen bundles in atherosclerotic plaques (Watson et al ., ) and in cardiac fibrosis after myocardial infarction (Hervas et al ., ). In skin research, lesional sclerodermic skin, nonlesional sclerodermic skin and control skin displayed different collagen bundle orientation and packing (de Vries et al ., ).…”
Section: Introductionmentioning
confidence: 99%